Characteristics of attitudes about aging in late adulthood - Tatarko, Kristina I. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article presents the characteristics of attitudes about aging in late adults and the reasons why individuals choose certain characteristics. Attitudes become a reference point for an individual in forming his or her own attitude and perception of aging. Social attitudes about aging are characterised by a pronounced representation of cognitive component characteristics. Includes a description of the appearance and changes in the body, social activity, relationships with others, personality traits of the individual, worldview, feeling /experience of age changes. The features of this process are artificially hyperbole. The study of attitudes towards aging will make it possible to formulate recommendations for individual passage through this period.